1998
DOI: 10.1038/sj.ejcn.1600564
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory quotient changes in full term newborn infants within 30 hours from birth before start of milk feeding

Abstract: Objective: To evaluate substrate utilization in full-term newborn infants, fed every 3±4 h with glucose 10% solution, within 30 h from birth. Design: Random. Setting: Full term newborn infants at the Paediatric Division City Major Hospital, Chair of Paediatrics, Verona University. Subjects: Forty-six newborn infants, 24 females and 22 males of 39 AE 2 weeks gestational age. Methods: Oxygen consumption (VO 2 ) and CO 2 production (VCO 2 ) were measured. Permitting the computation of the respiratory quotient (RQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…A reduction in the RQ value indicates a decreasing rate of carbohydrate metabolism and a shift towards alternative substrates such as proteins and particularly, fats. Previous studies have suggested that the quantity of proteins deposited is closely related to the protein intake, while the quantity of fat deposited is closely related to the energy intake [3]. Therefore, the RQ value provides a valuable indicator of a premature infant's energy intake.…”
Section: Biomedical Engineering-applications Basis and Communicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction in the RQ value indicates a decreasing rate of carbohydrate metabolism and a shift towards alternative substrates such as proteins and particularly, fats. Previous studies have suggested that the quantity of proteins deposited is closely related to the protein intake, while the quantity of fat deposited is closely related to the energy intake [3]. Therefore, the RQ value provides a valuable indicator of a premature infant's energy intake.…”
Section: Biomedical Engineering-applications Basis and Communicationsmentioning
confidence: 99%
“…Meanwhile , the generated carbon dioxide volume during the same period is approximately 6.305 ± 1.259 (ml/kg/min). Furthermore, newborn infants within 30 hours from birth and prior to the start of milk feed-in consume an oxygen volume of approximately 7.422 ± 1.241 (ml/kg/min), and generate a carbon dioxide volume of approximately 6.532± 1.091 (mUkg/min) [3]. Finally, it has been reported that the respiratory rate of newborn infants is approximately 40-60 breaths/min [3,12].…”
Section: Biomedical Engineering-applications Basis and Communicationsmentioning
confidence: 99%
“…An important metabolic indicator called the respiratory quotient ͑RQ͒ is used to represent the oxidized substrate. 15 RQ is determined by the ratio of V CO 2 to V O 2 , and the theoretical respiratory quotient of ethanol combustion is obtained as…”
Section: A Combustion Of Ethyl Alcoholmentioning
confidence: 99%